MARKETING COMMUNICATION THROUGH SOCIAL MEDIA INSTAGRAM: A CYBER MEDIA ANALYSIS - Anisyah Melani Sabrina; Petrus Ana Andung; Fitria Titi Meilawati (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2023)
The most successful social media for buying and selling activities is Instagram due to its ability to provide product content with a more attractive appearance so that users can be more comfortable when using it. This article discusses marketing communication patterns and consumer behavior during virtual shopping. This study uses an interpretive paradigm with a qualitative approach. Using a cyber media analysis, this study indicates that even through online buying and selling transactions, the pattern of marketing communication among the @kupang_kpopstuff admin and followers remains interactive. The admin utilized a digital catalog to reduce promotional costs. Meanwhile, consumer behavior is grouped into the 5A path, starting from the Aware stage, in which potential buyers were aware of the existence of @kupang_kpopstuff as a digital platform that provides K-Pop products. In the following stage, Appeal when prospective buyers are interested and eventually, follow Instagram @kupang_kpopstuff. The next consumer behavior was Ask; Followers searched for information by utilizing digital catalogs in the Instagram account. After that, followers took an attitude and or action (Act) to buy a product or not. The final stage of consumer behavior is Advocate where followers recommend K-Pop products to other people, especially other K-Pop fans.